The year 2000 computing crisis a millennium date conversion plan - Murray, Jerome T. (McGraw-Hill, 1996)
With the year 2000 fast approaching, you can't afford to put off the date conversion problem any longer. This essential, timely guide is the solution. With it, you'll have all the tools you need to avoid a systems meltdown.